Competência arquivística: um estudo de caso na comunidade remanescente de quilombo Igarapé Preto - SILVA, Érica dos Santos (2024)
This research aimed to understand the understanding of residents of the quilombola community of Igarapé Preto about the precepts of Archival Competence based on experiences, documents and archival processes. The question that guided the research is: do the precepts of Archival Competence relate to the experiences of subjects with archival documents and processes? It was decided to expand the discussions around the Sociocultural Context for the research, seeking definitions from other areas. To achieve the objective of the work, bibliographical research was carried out regarding the proposed themes and a case study carried out in that community. 10 people were interviewed, 7 females and 3 males aged between 13 and 58 years. In conclusion, the results indicate that these subjects are aware of the precepts of Archival Competence, but it is not possible to state that they fully have the knowledge and skills of Archival Competence based on Domain Knowledge, Artifact Competence and Archival Intelligence